Durability, Resilience and Sustainability in the Building Rehabilitation Process. Issue 3 (November 2021) - Dabija, Ana-Maria
Abstract: Where buildings are concerned, the term "sustainability" has been used for more than 30 years. It represents a process of designing, constructing and operating the building considering its environmental impact. A year after the major nuclear plant catastrophe from Chernobyl, the Brundtland Report defined sustainability as the actions that meet "the needs of the present without compromising the ability of future generations to meet their own needs". A different disaster, a natural one – the Katrina hurricane – led, two decades later, to the addition of another building characteristic: "resilience". It represents the capacity of a system to adapt after a shock. "Durability" may refer to different issues: the building materials, the building structure, its functionality of aesthetics. The more durable a building is - the more it lasts - the less it affects the environment. The more it lasts, the more resilient it is (as it withstands different types of stress). Technical durability, provided by building materials and structures, prevails over the functional durability. A good example is the case of the industrial buildings of the nineteenth century: constructed with solid masonry structures, these buildings have lost the original functions decades ago and they were subject of conversions that provided them a new life cycle. Withstanding the action of natural and anthropic agents, these buildings proved to be resilient and, by saving the natural resources, they can also be considered sustainable. Considering that in the next 30 years we will still face 70% of the current building stock, it is important how we deal with them, in order to provide, by rehabilitation, a new life cycle to the existing constructions. The paper tackles, from a critical perspective, some examples of good and bad practice in the building rehabilitation process.